A Prospective Comparative Study Between Early And Interval Laparoscopic/open Cholecystectomy In Patients Of Acute Cholecystitis (Indian Journal of Applied-Basic Medical Sciences, 2022)
OBJECTIVE: The present study is designed to compare early and interval laparoscopic/open cholecystectomy in patients of acute cholecystitis. The comparison was done on the basis of parameters such as intraoperative difficulty, perioperative bile duct injury and bile leak, time taken for operation, postoperative atelectasis, postoperative wound infection, duration of hospital stay and postoperative pain. METHODOLOGY: This is a prospective study conducted in Department of General surgery, GCS MEDICAL COLLEGE, HOSPITAL AND RESEARCH CENTRE from AUGUST 2018 to DECEMBER 2019. 56 patients were enrolled in the study from which 26 patients were randomly assigned to early lap/open cholecystectomy and 30 were assigned to interval lap/open cholecystectomy group. RESULT: There was no significant difference observed between the two groups. However, the duration of hospital stay was less in early laparoscopic/open cholecystectomy.  CONCLUSION: Both the methods, early and interval have no significant benefit over each other but through review of all literature, early lap/open cholecystectomy is found to be beneficial overall with less hospital stay.
Keywords: Early cholecystectomy; Interval cholecystectomy; laparos